Difficulties in generating specific antibodies for immunohistochemical detection of nitrosylated tubulins. - Anton Kamnev; Matthias Muhar; Martina Preinreich; Hermann Ammer; Friedrich Propst (PLoS ONE)
Protein S-nitrosylation, the covalent attachment of a nitroso moiety to thiol groups of specific cysteine residues, is one of the major pathways of nitric oxide signaling. Hundreds of proteins are subject to this transient post-translational modification and for some the functional consequences have been identified. Biochemical assays for the analysis of protein S-nitrosylation have been established and can be used to study if and under what conditions a given protein is S-nitrosylated. In contrast, the equally desirable subcellular localization of specific S-nitrosylated protein isoforms has not been achieved to date. In the current study we attempted to specifically localize S-nitrosylated α- and β-tubulin isoforms in primary neurons after fixation. The approach was based on in situ replacement of the labile cysteine nitroso modification with a stable tag and the subsequent use of antibodies which recognize the tag in the context of the tubulin polypeptide sequence flanking the cysteine residue of interest. We established a procedure for tagging S-nitrosylated proteins in cultured primary neurons and obtained polyclonal anti-tag antibodies capable of specifically detecting tagged proteins on immunoblots and in fixed cells. However, the antibodies were not specific for tubulin isoforms. We suggest that different tagging strategies or alternative methods such as fluorescence resonance energy transfer techniques might be more successful.